Customer Satisfaction : A Study on the Services Offered by Lembaga Urusan Tabung Haji (LUTH) in Makkah, Madinah and Mina - Wawaeni, Khalid (2009)
This study presents an attempt to examine the services offered by Lembaga Urusan Tabung Haji (LUTH) to Malaysian Hajj pilgrims. There are five types of services offered by LUTH which are lodging, health, food, transport and general services. A study was conducted in Makkah during 2008 Hajj pilgrims. The survey was conducted after the pilgrims completed their activity in Mina before completing their Hajj. From a total of 500 pilgrims 113 pilgrims responded which represent a response rate of 22.6 percent. A total of 500 questionnaires were distributed to Malaysian Hajj pilgrims at three hotels in Makkah. Descriptive analysis, mean and standard deviation were carried out on the data collected. The findings of this study suggest that the pilgrims are satisfied by the services provided by LUTH. However there are areas of services that can still be improved.